The fauna of the South China Sea include unknown phoronid species: new records of larvae and adults. Issue 5 (2nd September 2016) - Temereva, Elena N.; Neretina, Tatiana V.; Stupnikova, Alexandra N.
Abstract : The Phoronida is a phylum of marine invertebrates that have a worldwide distribution and that form huge benthic aggregations in many aquatic areas. Although there are only 11 recognized species of phoronids, many species clearly remain to be described. The matching of larval and adult stages of the same species will help indicate which larvae belong to described species and which represent undescribed species whose adults have yet to be found. Larvae of four phoronid species were collected in Nha Trang Bay and investigated by light microscopy and molecular methods. Three of the described larvae belong to new phoronid species that have yet to be named. These larvae have unique morphological features and occupy separate positions on the phylogenetic tree of phoronids. One of the described larvae belongs to Phoronis hippocrepia or to a closely related species. Observations made with a new macrophotographic method indicated that Phoronopsis californica also occurs in Nha Trang Bay. Thus, according to records of larvae and adults, Nha Trang Bay contains at least nine phoronid species: Phoronopsis californica, Phoronopsis malakhovi, Phoronis australis, Phoronis hippocrepia (or a closely related species), three unknown phoronid species whose larvae have unique morphological features and that apparently belong to the genus Phoronis, and two species, whose adults have unique set of morphological features. The richness of phoronids in this area suggests that the Indo-Pacific is a centre of phoronid biodiversity.